Adherence to Covid-19 vaccination during the pandemic: the influence of fake news - Luana Cristina Roberto Borges; Sonia Silva Marcon; Gabrielly Segatto Brito; Miriam Terabe; Nathalia Ivulic Pleutim; Ana Heloisa Mendes; Elen Ferraz Teston (Associação Brasileira de Enfermagem, 2024)
ABSTRACT Objectives: to understand how fake news has influenced adherence to Covid-19 immunization, from the perspective of health professionals. Methods: a qualitative, descriptive-exploratory study was conducted in Campo Grande - MS. Twenty nursing professionals working in vaccine rooms or managing immunobiologicals participated through semi-structured interviews. The interviews were audio-recorded, fully transcribed, and subjected to thematic content analysis. Results: two categories emerged in which the professionals highlighted an increase in vaccine hesitancy among the population, influenced by fake news and denialist actions, which negatively interfered with the population's trust in vaccines and in the professionals administering them. Final Considerations: concerns about vaccine safety and denialist actions by authorities and media outlets can contribute to the phenomenon of non-vaccination. The valorization of science, the promotion of educational actions, and raising public awareness about immunization were presented as strategies to increase vaccine coverage